BORDER LEGALIZATION UNDER INTERNATIONAL LAW AS A REGIONAL SECURITY FACTOR IN CENTRAL ASIA - BOBOKULOV, Inomzhon (CENTRAL ASIA AND THE CAUCASUS, 2011)
The rapid changes occurring in today’s world cannot help but have an impact on the traditional perception of the state’s role in international relations. While criticizing the principle of state sovereignty (as the central idea of statehood) and presenting numerous facts testifying to its erosion, contemporary researchers are coming up with alternative conceptions such as “a world without borders,” “the end of geography,” and so on. However, at the current stage of globalization, the border is still one of the most important fundamental principles of the inviolability of a state’s territorial integrity, that is, an indispensable condition of its existence. Despite all the assertions of a “decline in sovereignty,” at the beginning of the 21st century, “thousands are prepared to die for the creation of new state borders.”1From the perspective of international law, the border, while helping to prevent interstate conflicts, on the one hand, is a factor in their emergence, on the other. As a rule, territorial disputes arise between states over title to a particular territory (or part of it). International law maintains the territorial status quo and strengthens international security; and it is “the most appropriate moral answer to territorial conflicts.”2 In contrast to other methods for determining the border line (historical, geographical, economic, ethnic, etc.) or territorial title, legal regulations establish the boundaries of state power over the specified territory. Borders form an essential part of the structure of rules and institutions that enable separate political communities to coexist.3An analysis of the current state of interstate practice in Central Asia (CA) shows that in addition to the distribution of shared hydropower resources, settlement of the Afghan crisis, and combating current threats to security, unresolved border and territorial issues are the most urgent problems of international law hindering the creation of the necessary conditions for establishing mutually advantageous cooperation in the region.In our opinion, the following three main factors can be singled out among the factors promoting delimitation and demarcation of state borders in CA.